(untitled) (Nordic Journal of African Studies, 2005)
Recording and analysing a language in a natural setting provides ample sources of empirical materials to linguists and ethnographers. Yet, competing opinions arise as to the best method to undertake such endeavour without risking the inherited weakness of the direct elicitation. In this article, I provide three narrative texts of a previously unknown Swahili dialect of Kingome, as currently spoken in Mafia Island, Southern Tanzania, as evidence that ethnographic approach is suitable to record and document ethically sensitive themes that often preserve much sought language and culture heritages of the isolated communities.